SMEs Financing as an Important Factor of Business Environment in Slovak Republic Regions - Eva Koisova (Montenegrin Journal of Economics, 2017)
The aim of every healthy economy is to reduce differences between regions in economic life, living standards and employment. It is a difficult task for most countries and especially in the Slovak Republic, because of the hard-pressed situation in decreasing regional differences. Paper's aim was to determine whether from a regional perspective, exist differences between entrepreneurs' opinion in obtaining loans in Slovak banks. In this context; we focused on the perception of bank involvement with SMEs, the transparency of bank lending, the information gap in bank loan terms and perception of the contemporary loan terms compared with the past ones. We conducted the survey on the sample of 541 respondents, in 2016. We found that more than one-half of them did not believe in bank transparency and about the same number considered information gap as significant. Approximately 60% of entrepreneurs thought that credit conditions are more acceptable than the past ones.